2020
DOI: 10.1002/bse.2700
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management practices and financial performance using data envelopment analysis in Japan: The mediating role of environmental performance

Abstract: This study investigates the relationship between environmental management practices (EMPs) and financial performance (FP) and consequently ascertains whether environmental performance (EP) can mediate the EMPs-FP nexus. Distinctly using data envelopment analysis and generalised method of moments techniques to analyse a comprehensive dataset of Nikkei 225 listed firms from 2007 to 2018 (1920 firm-year observations), our findings first suggest that EMPs have a positive effect on FP. Second, the desired EP can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 131 publications
(363 reference statements)
7
44
0
4
Order By: Relevance
“…Environmental practices, in turn, can lead to environmental performance because a higher development of these practices makes their adoption improve their efficiency, improving environmental performance (Testa et al, 2018). Although prior empirical studies have shown both positive (Hartmann & Vachon, 2018) and no positive associations (Delmas & Toffel, 2004) between environmental practices and environmental performance, it is expected that environmental practices enhance environmental performance (Aslam, Elmagrhi, Rehman, & Ntim, 2020; Fuzi, Habidin, Janudin, & Ong, 2019; Mungai, Ndiritu, & Rajwani, 2020) because these practices help to reduce environmental hazards and water and other resources and material consumption. Environmental practices such as those related to save water and energy, reduction in emissions, employee training, and the measurement of environmental costs and savings allow companies to reduce materials, water and energy consumption, pollution emission, and waste production levels and improvements regarding a more efficient use of the resources needed to manufacture the products (Chaudhuri & Jayaram, 2019; Wagner, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Environmental practices, in turn, can lead to environmental performance because a higher development of these practices makes their adoption improve their efficiency, improving environmental performance (Testa et al, 2018). Although prior empirical studies have shown both positive (Hartmann & Vachon, 2018) and no positive associations (Delmas & Toffel, 2004) between environmental practices and environmental performance, it is expected that environmental practices enhance environmental performance (Aslam, Elmagrhi, Rehman, & Ntim, 2020; Fuzi, Habidin, Janudin, & Ong, 2019; Mungai, Ndiritu, & Rajwani, 2020) because these practices help to reduce environmental hazards and water and other resources and material consumption. Environmental practices such as those related to save water and energy, reduction in emissions, employee training, and the measurement of environmental costs and savings allow companies to reduce materials, water and energy consumption, pollution emission, and waste production levels and improvements regarding a more efficient use of the resources needed to manufacture the products (Chaudhuri & Jayaram, 2019; Wagner, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Second, studies investigating whether and how board structure variables can influence corporate environmental performance are scarce (De Villiers et al, 2011;Elmagrhi et al, 2019;García-Martín & Herrero, 2020;Rupley, Brown, & Marshall, 2012), which limit current knowledge relating to the influence of board structures on firms' environmental performance. Third, these few environmental performance studies are impaired in that they have largely been conducted in the context of developed countries, such as Australia (Rao, Tilt, & Lester, 2012), United States (De Villiers et al, 2011;Post, Rahman, & McQuillen, 2015;Rupley et al, 2012), EU (García-Martín & Herrero, 2020), Japan (Aslam, Elmagrhi, Rehman, & Ntim, 2020) and United Kingdom (Brammer & Pavelin, 2006, 2008Liao et al, 2015), with relatively less attention being paid to environmental performance in the context of developing/emerging economies in general (Alnabsha, Abdou, Ntim, & Elamer, 2018;Haladu & Salim, 2016;Iatridis, 2013) and in China in particular, where environmental problems (i.e., land degradation, air and water pollution and deforestation) have posed significant threat to public lives and health (Elmagrhi et al, 2019;Shahab et al, 2020). Fourth, prior studies have examined the impact of a small number of board structure variables, such as board gender diversity (Ben-Amar, Chang, & McIlkenny, 2017;Harjoto, Laksmana, & Lee, 2015) and board independence (Brammer & Pavelin, 2008) on firms' environmental performance.…”
mentioning
confidence: 99%
“…Recently, scholars raise a concern that the link between ES and FP is influenced by mediators (Li, Jayaraman, Paulraj, & Shang, 2016). Consistently, some studies reveal that EP is the mediator on the link between environmental management practices and FP (Aslam, Elmagrhi, Rehman, & Ntim, 2021;Feng, Yu, Wang, Wong, Xu, & Xiao, 2018). These findings can be drawn upon the natural resource-based view (NBRV) (Hart, 1995), which indicates that enterprises can sustain their competitive advantages when they align their operations in line with the protection of the natural environment .…”
Section: Introductionmentioning
confidence: 94%
“…In this regard, this study contributes to the environmental management literature by addressing the mediating role of EP when examining the indirect effects of ES on FP. In addition, this study also contributes to the growing body of environmental management research, which draws from NRBV to propose the research framework (see Clemens & Bakstran, 2010) examining the mediating effect of EP (Aslam et al, 2021;Feng et al, 2018). Second, although the positive effect of ES has been examined in the context of TPLSPs recently, there is still a lack of understanding, which demands more insight.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation